The Effect of Using Different Ball Weights and Sizes on Developing Some Fundamental Skills in Soccer - Jaleel, Kahtan; Radi, Saleh; Salman, Ali (Journal of Physical Education, 2020)
The research aimed at identifying the effect of using exercises with different ball sizes and weights on developing some fundamental skills in soccer players aged 9 – 10 years old. The researchers used the experimental method on (20) soccer players from Amo Baba Soccer School. The subjects were equally divided into two groups. The results showed that using different ball weights and sizes have positive effects on fundamental skill development and significantly improving the level of performance in the experimental group that used ball with lesser weights and smaller size compared to the controlling group. The researchers recommended that coaches and supervisors should use balls of different weights and sizes when teaching soccer to younger age groups U10.